Inland wetlands mapping and vulnerability assessment using an integrated geographic information system and remote sensing techniques - C.E. Akumu; J. Henry; T. Gala; S. Dennis; C. Reddy; F. Tegegne; S. Haile; R.S. Archer (Global Journal of Environmental Science and Management)
The understanding of inland wetlands’ distribution and their level of vulnerability is important to enhance management and conservation efforts. The aim of the study was to map inland wetlands and assess their distribution pattern and vulnerability to natural and human disturbances such as climate change (temperature increase) and human activities by the year 2080. Inland wetland types i.e. forested/shrub, emergent and open water bodies were classified and mapped using maximum likelihood standard algorithm. The spatial distribution pattern of inland wetlands was examined using average nearest neighbor analysis. A weighted geospatial vulnerability analysis was developed using variables such as roads, land cover/ land use (developed and agricultural areas) and climate data (temperature) to predict potentially vulnerable inland wetland types. Inland wetlands were successfully classified and mapped with overall accuracy of about 73 percent. Clustered spatial distribution pattern was found among all inland wetland types with varied degree of clustering. The study found about 13 percent of open water bodies, 11 percent of forested/shrub and 7 percent of emergent wetlands potentially most vulnerable to human and natural stressors. This information could be used to improve wetland planning and management by wetland managers and other stakeholders.